(untitled) (Research, Society and Development, 2020)
The Health System in Brazil is divided into Public System and Private or Supplementary System. The health system is considered supplementary because it markets health plans and sells services already covered by the public system, called the Universal Health System (SUS), offering some additional elements. In order to answer the research question “Is verticalization feasible when outsourcing health services?” We will use the multiple case study. The research leads us to conclude that verticalization may be more viable due to the outsourcing of health services, once the costs with the own network become lower than the costs with the accredited network. Mainly regarding MatMed and OPME costs, whose percentage difference is 30% for the different networks.